A Review on Electrospun Nanofibres for Drug Delivery - Kamala Kumari (Journal of Global Pharma Technology, 2020)
Electrospinning is most widely used technique for fabrication of nanofibres. It is cost effective, simple and versatile process. The resulting nanofibres possess unique properties such as a high surface-area-to-volume and aspect ratio, low density, and high pore volume. These properties make the nanomaterials more advantageous than conventional materials in energy harvesting, conversion, and storage devices. There are different aspects of electrospinning, but the current discussion is based on the use of electrospun fibrous matrices for drug delivery. The article explains about all the available approaches to incorporate drugs onto or within electrospun fibrous matrices, along with their release mechanisms and about the applications of such drug carrying fibrous matrices for regeneration of various tissues, such as neural, vascular, cardiac, skin, and bone.